Mild autonomous cortisol secretion leads to reduced volumetric BMD at lumbar spine in patients with primary aldosteronism - Mansour, Nabeel; Bruedgam, Denise; Heinrich, Daniel; Dischinger, Ulrich; Reisch, Nicole; Völter, Friederike; Stüfchen, Isabel; Nowak, Elisabeth; Zopp, Stephanie; Vasileva, Victoriya; Öcal, Osman; Wildgruber, Moritz; et al. (Frontiers in Endocrinology, 2024)
Objectives Glucocorticoid cosecretion is more common in primary aldosteronism (PA) than previously thought. Chronic subtle cortisol excess in patients with mild autonomous cortisol cosecretion (MACS) negatively affects bone health. This study aimed to evaluate the impact of MACS on bone density and turnover markers in PA patients. Methods Patients with PA and MACS (n = 50), confirmed by a 1-mg dexamethasone suppression test (DST) with a cortisol cutoff of ≥1.8 µg/dL without symptoms of overt Cushing, were compared to age- and sex-matched patients with PA without MACS (non-MACS, n = 50). Lumbar volumetric bone mineral density (vBMD) was extracted by a novel convolutional neural network (CNN)-based framework (SpineQ software v1.0) applied to routine CT data, incorporated into the diagnostic protocol for PA. Additionally, bone turnover markers—including osteocalcin, bone-specific alkaline phosphatase, N-terminal propeptide of type I collagen, and carboxy-terminal crosslinked telopeptide of type I collagen were evaluated between the groups. Results Median cortisol after DST was 1.1 µg/dL (30.3 nmol/L) [IQR: 0.5 µg/dL (13.8 nmol/L)] in the non-MACS group and 2.5 µg/dL (69.0 nmol/L) [IQR: 1.4 µg/dL (38.5 nmol/L)] in the MACS group (p < 0.001). Patients with MACS had significantly lower vBMD values compared to the non-MACS group (106.4 mg/cm³ vs. 116.6 mg/cm³, p = 0.038). Cortisol after DST negatively correlated with vBMD (Spearman’s r=−0.33, p=0.00042). No significant differences in bone turnover markers were found, and classifications based on visible lesions on CT or PA-lateralization via adrenal venous sampling did not reveal any significant differences in these markers (p > 0.05 for all comparisons). Conclusion Despite nonsignificant differences in bone turnover markers between patients with PA with or without MACS, CT scans revealed significantly reduced vBMD in PA and MACS patients, indicating compromised bone health and vBMD significantly negatively correlated to cortisol post DST. Thus, opportunistic evaluation of vBMD in routine CT screenings could aid in the early detection of bone alterations in MACS and help mitigate potential long-term adverse effects on bone health.